Barium nanotitanate microwave ceramics obtained by a chemical method - Castro, Pedro J.; Zanetti, Sonia M. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Dielectric resonators with high dielectric constant, low dielectric losses and high frequency stability have been widely used in microwave circuits for telecommunications as filters, oscillators, antennas. Among the compounds of the BaO-TiO2 system, Ba2Ti9O20 has met these requirements. However, such materials are difficult to obtain by conventional mechanical powder mixture due to the preferential formation of secondary phases and high sintering temperatures around 1300°C. In this investigation a new approach for obtaining B2O3-added Ba2Ti9O20 is considered through a chemical method involving a co-precipitation process aiming to reduce the sintering temperature and to promote a high microstructural homogeneity of the compound. Therefore, cylindrical ceramics were sintered at 1000-1150°C presenting values of electric permittivity from 34.8 to 41.4, quality factor due to dielectric losses from 2945 to 3525, temperature coefficient from 6.2 to 10.2 ppm/°C and an overall tunable frequency range of 5.00-7.00 GHz, which yields promising properties for use as dielectric resonators. © 2013 IEEE.
Keywords: barium nanotitanate; dielectric resonators; microwave ceramics; microwave properties